2014
DOI: 10.1177/0954411914554244
|View full text |Cite
|
Sign up to set email alerts
|

ASTM F1717 standard for the preclinical evaluation of posterior spinal fixators: Can we improve it?

Abstract: Preclinical evaluation of spinal implants is a necessary step to ensure their reliability and safety before implantation. The American Society for Testing and Materials reapproved F1717 standard for the assessment of mechanical properties of posterior spinal fixators, which simulates a vertebrectomy model and recommends mimicking vertebral bodies using polyethylene blocks. This set-up should represent the clinical use, but available data in the literature are few. Anatomical parameters depending on the spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(97 citation statements)
references
References 63 publications
3
92
1
1
Order By: Relevance
“…A simplified implant design was assumed [18]. Screws were positioned within the pedicles according to their orientation with respect to the anatomical planes; moreover, the spinal rod shape was drawn to follow the natural curvature of the lordotic segment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A simplified implant design was assumed [18]. Screws were positioned within the pedicles according to their orientation with respect to the anatomical planes; moreover, the spinal rod shape was drawn to follow the natural curvature of the lordotic segment.…”
Section: Methodsmentioning
confidence: 99%
“…A simplified implant design was assumed [18] and the pedicle screws were introduced within the test blocks (Fig. 1).…”
Section: Fe Models Of Current Standardsmentioning
confidence: 99%
“…Nevertheless, the experiment outcomes cannot predict the actual situation of in vivo application of the modified DACBP system. In the literature, the complications concerning the front cervical plate are restricted to releasing or breaking of the equipment and tracheoesophageal or neurovascular auxiliary wounds [16]. Different sorts of complications that may prompt to clinical indications are overlooked, and the emphasis is fundamentally made on unconstrained plates [17].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the slackening of rod-screws occurs through a cross-split screw head that can be fastened into the biomaterial plate [1,2]. Vertebral compression in the back of the body causes 1.4 million fractures in the musculoskeletal system worldwide [3]. In this study, a most negative scenario of vertebrectomy situation was applied, where the implant inserts are embedded in vertebral body-like pieces and need to bear presso-flexion.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebral compression in the back of the body causes 1.4 million fractures in the musculoskeletal system worldwide [3].…”
Section: Introductionmentioning
confidence: 99%